A New Dyspnea Evaluation System Focusing on Patients’ Perceptions of Dyspnea and Their Living Disabilities: The Linkage between COPD and Frailty - Oishi, Keiji (J Clin Med, 2020)
Background: As much as there are unmet needs for brief frailty assessment in patients with chronic obstructive pulmonary disease (COPD), the lack of a simplified and comprehensive dyspnea evaluation system that focuses on the patients’ perceptions of dyspnea and their COPD living disabilities remains a major challenge. We developed patient-reported outcome measures for dyspnea-related behavior and activity limitation (PROMs-D), which consisted of the Activity-limit Dyspnea Scale (ADS) and Self-Limit Dyspnea Scale (SDS), while investigated the usefulness of PROMs-D in identifying frailty. Methods: We administered PROMs-D and frailty status evaluations in 128 outpatients. Results: We classified 30 (23.4%), 50 (39.0%), and 48 (37.5%) patients as robust, prefrail, and frail, respectively. There was a positive correlation between SDS and ADS (ρ = 0.67, p < 0.001), and both ADS and SDS had high accuracies for detecting frailty (AUC, 0.82 and 0.78, respectively). Moreover, a PROMs-D score that consisted of the sum of ADS and SDS was more effective in stratifying frailty (cutoff value, 2; AUC, 0.85; sensitivity, 60%; specificity, 95%). Conclusions: PROMs-D could be used as the first step for frailty screening in patients with COPD, and we propose the importance of capturing the troublesome nature of living behaviors due to dyspnea in daily clinical practice.